The Effectiveness of Mime-Based Creative Drama Education for Exploring Gesture-Based User Interfaces - Unluer, Adviye Ayca; Baytas, Mehmet Aydin; Buruk, Oguz Turan; Cemalcilar, Zeynep; Yemez, Yucel; Ozcan, Oguzhan (WILEY, 2018)
User interfaces that utilise human gestures as input are becoming increasingly prevalent in diverse computing applications. However, few designers possess the deep insight, awareness and experience regarding the nature and usage of gestures in user interfaces to the extent that they are able to exploit the technological affordances and innovate over them. We argue that design students, who will be expected to envision and create such interactions in the future, are constrained as such by their habits that pertain to conventional user interfaces. Design students should gain an understanding of the nature of human gestures and how to use them to add value to UI designs. To this end, we formulated an awareness course' for design students based on concepts derived from mime art and creative drama. We developed the course iteratively through the involvement of three groups of students. The final version of the course was evaluated by incorporating the perspectives of design educators, an industry expert and the students. We present the details of the course, describe the development process, and discuss the insights revealed by the evaluations.
Keywords: design education; user interface design; gestural interaction; creative drama; mime art; DESIGN; Art; Education & Educational Research